Substitution between Production Labor and Other Inputs in Unionized and Nonunionized Manufacturing: Comment - Chi, Hua-Shan (The Review of Economics and Statistics, 1989)
Hua-Shan Chi, Substitution between Production Labor and Other Inputs in Unionized and Nonunionized Manufacturing: Comment, The Review of Economics and Statistics, Vol. 71, No. 3 (Aug., 1989), pp. 549-552